Development of Human-Robot Interaction System (HRIS) using autonomous programmable humanoid robot and motion sensing input device / Wan Zharfan Wan Zainal Abiddin, Rozita Jailani and Abdul Rahman Omar - Wan Zainal Abiddin, Wan Zharfan; Jailani, Rozita; Omar, Abdul Rahman (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper presents the development process of Human-Robot Interaction System (HRIS) based on movement imitation using autonomous programmable Humanoid Robot NAO and Microsoft Kinect Motion Sensor. This interactive platform enables autistic children and Humanoid Robot NAO to imitate each other in real time aided by Microsoft Kinect Sensor for skeletal tracking movement. Then, all the required information is uploaded to online server for therapists' evaluation. Pilot test has been performed to evaluate the performance of HRIS in imitation therapy session. The session has been tested with normal healthy children where they imitate Humanoid Robot NAO movement with reference to several different upper body posture.